Connections on central extensions, lifting gerbes, and finite-dimensional obstruction vanishing - Biswas, I; Upmeier, M (American Mathematical Society, 2021)
Given a central extension of Lie groups, we study the classification problem of lifting the structure group together with a given connection. For reductive structure groups we introduce a connective structure on the lifting gerbe associated to this problem. Our main result classifies all connectionson the central extension of a given principal bundle. In particular, we find that admissible connections are in one-to-one correspondence with parallel trivializations of the lifting gerbe. Moreover, we prove a vanishing result for Neeb’s obstruction classes for finite-dimensional Lie groups.